Research on Advertising Creative Strategies for Shenyang Subway in the Era of Media - Zhu, Xiaona (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of information technology, the era of media convergence has arrived, and its profound influence has penetrated into every corner of the advertising industry. In this context, the advertising on Shenyang subway, as an essential part of urban public transportation advertising, has also encountered challenges and opportunities in terms of its creative strategies and expression methods. This article will conduct an in-depth analysis of the current status of advertising creative strategies on Shenyang subway and propose corresponding optimization suggestions to promote innovative development in this industry.